The Roles of RNA N6-Methyladenosine in Regulating Stem Cell Fate - Ji, Runbi; Zhang, Xu (Frontiers in Cell and Developmental Biology, 2021)
RNA N6-methyladenosine (m6A) modification has important regulatory roles in determining cell fate. The reversible methylation process of adding and removing m6A marks is dynamically regulated by a fine-tuned coordination of many enzymes and binding proteins. Stem cells have self-renewal and pluripotent potential and show broad prospects in regenerative medicine and other fields. Stem cells have also been identified in cancer, which is linked to cancer metastasis, therapy resistance, and recurrence. Herein, we aimed to review the molecular mechanism that controls the reversible balance of m6A level in stem cells and the effect of m6A modification on the balance between pluripotency and differentiation. Additionally, we also elaborated the association between aberrant m6A modification and the maintenance of cancer stem cells in many cancers. Moreover, we discussed about the clinical implications of m6A modification in cancer stem cells for cancer diagnosis and therapy.